Claiming the Holy: The Legacy of Jesus as a Folk Hero in Rabbinic and Ecclesiastic Literature after the First Council of Nicaea - Sela, Gal (Review of ecumenical studies, 2025)
This article explores the cultural background and doctrinal formation of Jesus at the First Council of Nicaea within the broader discourse on the holy man in late antiquity. In the Roman Empire, the figure of the charismatic miracle worker emerged as a popular religious folk hero, a pattern evident in monastic, ecclesiastical, and rabbinic literature. The paper investigates the conditions that enabled the emergence and spread of such a figure within Jewish and Christian communities after the destruction of the Second Temple. It argues that the terminology adopted at Nicaea to define the divine nature of the Holy Son was shaped, in part, by the need to distinguish Jesus from the broader phenomenon of the charismatic holy man. By examining traditions of rainmaking asceticism and comparing Honi the Circle Maker and Simeon the Stylites in canonized fifth-century texts, this study analyzes how the holy man was appropriated into both rabbinic and ecclesiastical discourses.